DETERMINAN INDEKS PEMBANGUNAN MANUSIA DENGAN PENDEKATAN MAQASHID SYARIAH ASY-SYATIBI: DI JAWA TIMUR - Syahidah, Syahda Azmi; Wangi, Laila Campaka (ITB AAS INDONESIA Surakarta, 2025)
Indonesia is currently in an era of demographic dividend, which is expected to peak in 2035, when the majority of the population will be of productive age. This bonus is both an opportunity and a challenge, especially in the context of human development. This study aims to analyze the influence of five elements of Maqasid Shariah, namely Hifdz Ad-Din, Hifdz An-Nafs, Hifdz Al-Aql, Hifdz An-Nashl, and Hifdz Al-Mal on the Human Development Index (HDI) in 36 districts/cities in East Java in the period 2016-2020. Using panel data analysis and fixed effect model (FEM) method, the study found that Hifdz An-Nafs (health budget) and Hifdz An-Nashl (total population) have a significant positive effect on increasing HDI, while Hifdz Al-Aql (education budget) and Hifdz Al-Mal (GRDP per capita) have a positive but insignificant effect. On the other hand, Hifdz Ad-Din has a significant negative effect on HDI, indicating that increasing crime rates have an impact on reducing HDI. This research provides new insights into the integration of Sharia values into development strategies to create sustainable material and spiritual well-being.